2021
DOI: 10.3390/pharmaceutics13122133
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and Modeling of Plasmonic Photothermal Therapy Delivered via a Fiberoptic Microneedle Device Ex Vivo

Abstract: Plasmonic photothermal therapy (PPTT) has potential as a superior treatment method for pancreatic cancer, a disease with high mortality partially attributable to the currently non-selective treatment options. PPTT utilizes gold nanoparticles infused into a targeted tissue volume and exposed to a specific light wavelength to induce selective hyperthermia. The current study focuses on developing this approach within an ex vivo porcine pancreas model via an innovative fiberoptic microneedle device (FMD) for co-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 55 publications
0
1
0
Order By: Relevance
“…The two biocompatible polymers used in this study were polycaprolactone (PCL) and polylactic acid (PLA), which were mixed with RhB to form the PCRS devices. The PCL was approved by the Food and Drug Administration (FDA) to be utilized as an implantable device due to its high biocompatibility and harmless biodegradation [ 28 , 29 , 30 ]. It was selected due to its melting point of 60 °C, malleability, and capacity to be 3D printed [ 31 , 32 , 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…The two biocompatible polymers used in this study were polycaprolactone (PCL) and polylactic acid (PLA), which were mixed with RhB to form the PCRS devices. The PCL was approved by the Food and Drug Administration (FDA) to be utilized as an implantable device due to its high biocompatibility and harmless biodegradation [ 28 , 29 , 30 ]. It was selected due to its melting point of 60 °C, malleability, and capacity to be 3D printed [ 31 , 32 , 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…One study compared the impact of two distinct wavelengths on the photothermal treatment of pancreatic tissues. This research revealed that, under identical conditions, the temperature generated by AuNPs at 808 nm was 200% higher than at 1064 nm, resulting in less damage to adjacent normal tissues [ 113 ]. Zhang et al utilized perfluorocarbon (PFC) as an oxygen carrier, aiming to replenish oxygen in the hypoxic environment of PC for PDT [ 114 ].…”
Section: Applications Of Aunps In the Treatment Of Pcmentioning
confidence: 99%